PENENTUAN KADAR FORMALDEHIDA DALAM TAHU SECARA KOLORIMETRI MENGGUNAKAN PEREAKSI SCHRYVER - 'ulya, Nikmatul
Tofu is a fresh processed food made of soybeans with high protein content widely consumed by many people in Indonesia. As a fresh processed food, the shelf life of tofu is only 1-2 days. However, there are many cases of misuse of hazardous substances, especially that of formaldehyde, which is added into tofu or its marinating liquid to improved elasticity and or to preserve this products. The aims of this research were to obtain an analytical method for determination of formaldehyde in tofu by means of Schryver method and data of formaldehyde content in tofu from various sales locations. Tofu sample was homogenised and acidified by addition of 10% phosporic acid solution. The sample was then distilled and the distillate was neutralized with sodium hydroxide solution to resulte in analyte solution. This solution was reacted with Schryver reagent to form red solution measurable by UV-Vis spectrophotometer at maximum wavelength of 518 nm. Analytical method was validated and determination of formaldehyde in sample was performed. Measurement of formaldehyde standard solutions resulted in a linear calibration curve of y = 0.0864 x + 0.0203 with correlation coefficient (r) of 0.9996. Limit of detection (LOD) and limit of quantitation (LOQ) of the method was 0.24 and 0.66 µg/mL, respectively. Method precision stated as coefficient of variance (CV) of intraday measurements were 3.323 and 2.659 %, respectively. Recovery percentage of standard additions at the concentration levels of 104.91, 100.78 and 95.13%. The concentration of formaldehyde in tofu sample from various sales locations, were in the range of 0.9- 6.3µg/gr with the average concentration of 1.7 µg/gr. Based on these results, it was concluded that an analytical method for determination of formaldehyde in tofu and data of formaldehyde in this product from various sales location were succesfully obtained.